Translating translated modernism an analysis of selected Korean-English translations of Yi Sang's works in the 1930s - Choi, Seong-Woo (2010)
This is a study on the "decontextualization" and "recontextualization" of Korean modernism by way of analyzing some selected English translated texts of Yi Sang's. Yi Sang is a representative Korean modernist poet and writer in colonial Korea of the 1930's. This study is, therefore, a translation criticism paying attention to translational "shifts" and "norms" in the target texts, and considering their relevance in conveying the qualities of Korean modernism to the English-speaking readers. Korean modernism is the result of adopting Western modernist literary thoughts and styles indirectly through Japan, more advanced in the importation of Western modernity. This is a kind of "translation," and can be called "translated modernism." Modernity is essential to the development of modernism because the latter represents and responds to the former. Korean modernism stemmed from "colonial modernity" which sprung during the Japanese regime in the early 20th century. Korean modernist writers, therefore, mimicked Western and Japanese modernisms, and consciously became ambivalent and mentally hybrid. Yi Sang's literary works contain these features of Korean modernism - frequent use of foreign words, coined words written in Chinese characters, and literary forms borrowed from Japan, as well as resistance against traditions, trials of experimental techniques, and destruction of old literary forms. This study analyzes the English translated texts by comparing them with the originals, in order to determine whether or not the translators were aware of the unique features of Korean modernism and how they tried to render them into English. With knowledge of Korean language and understanding of Korean general culture as bases, this study focuses on how the English translated texts keep intact the heterogeneity, schizophrenia and intertextuality of Yi Sang's original works.
"March 2010."
Thesis (M.A. Comparative Literature)--University of the Philippines Diliman.
Keywords: Korean literature -- Translations into English; Modernism (Literature) -- Korea; Contrastive linguistics